Incentive-driven decision-making networks in de novo and drug-treated Parkinson's disease patients with impulsive-compulsive behaviors: A systematic review of neuroimaging studies. (September 2020) - Martini, Alice; Tamburin, Stefano; Biundo, Roberta; Weis, Luca; Antonini, Angelo; Pizzolo, Clara; Leoni, Giuseppe; Chimenton, Silvia; Edelstyn, Nicola M.J.
Abstract: Background: In Parkinson's disease (PD), impulsive-compulsive behaviors (ICBs) may develop as side-effect of dopaminergic medications. Abnormal incentive-driven decision-making, which is supported by the cognitive control and motivation interaction, may represent an ICBs signature. This systematic review explored whether structural and/or functional brain differences between PD patients with vs without ICBs encompass incentive-driven decision-making networks. Methods: Structural and functional neuroimaging studies comparing PD patients with and without ICBs, either de novo or medicated, were included. Results: Thirty articles were identified. No consistent evidence of structural alteration both in de novo and medicated PD patients were found. Differences in connectivity within the default mode, the salience and the central executive networks predate ICBs development and remain stable once ICBs are fully developed. Medicated PD patients with ICBs show increased metabolism and cerebral blood flow in orbitofrontal and cingulate cortices, ventral striatum, amygdala, insula, temporal and supramarginal gyri. Abnormal ventral striatum connectivity with anterior cingulate cortex and limbic structures was reported in PD patients with ICBs. Discussion: Functional brain signatures of ICBs in PD encompass areas involved in cognitive control and motivational encoding networks of the incentive-driven decision-making. Functional alterations predating ICBs may be related to abnormal synaptic plasticity in these networks. Highlights: Functional changes predate impulsive-compulsive behavior in Parkinson's disease. Functional changes involve motivation-cognitive control networks in medicated patients. Structural changes are not consistently reported. Motivation-cognitive control networks regulates incentive-driven decision-making.